An Analysis of Philippine Trade Reforms in 1995-2000 Using the 1994 APEX Model - Caesar B. Cororaton; Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2000)
There are three major developments in the area of foreign trade in 1990s: (a) the WTO-Uruguay Round agreement in 1995; (b) the AFTA agreement; and (c) the series of unilateral trade reform programs of the government. The paper attempts to make an impact assessment of these reforms during the period 1995 and 2000 using the updated APEX model, a computable general equilibrium of the Philippine economy. Part of the trade reform process is the shift to transaction valuation of imports. The paper also attempts to analyze the possible effects of this shift.
Keywords: 330; policy analysis; planning tools and monitoring systems; economic/development modelling; trade reforms; Handelsliberalisierung; Allgemeines Gleichgewicht; Zollpolitik; Außenhandelspreis; Philippinen